The effect of community water fluoridation cessation on children's dental health: a national experience - Guy Tobias; Findler Mordechai; Chackartchi Tali; Bernstein Yaron; Greenberg Parizer Beatrice; Mann Jonathan; Sgan-Cohen Harold (BMC, 2022)
Abstract Background Community water fluoride (CWF) is the proven cornerstone of primary dental health care promotion. In 2002 CWF was made mandatory at a national level in Israel, however a new government revoked these regulations in August 2014. "Maccabi" is the second largest national health care provider with 2.3 million members, "Maccabi-Dent", its dental branch, has 53 clinics, employing 1100 dentists. The aim of this study was to evaluate the cumulative effect on treatment rates 6 years after CWF was terminated in Israel, based on the number of dental treatments provided to children aged 3-12 years in "Maccabi-Dent" clinics. Methods For this retrospective study, computerized dental treatment codes were collected. The "rate of treatment" was calculated by dividing the number of restorative treatments or extractions, by the number of individuals receiving treatment. The population size and the age group visiting the specific clinic were also considered. Results The independent variables were fluoride concentration in drinking water, age and socioeconomic position (SEP). There was a significant increase in restorative dental treatments after 2014, (R2 = 0.0402), with approximately twice the number of treatments required in the absence of CWF. Age had a significant association (β =  − 0.389, p < 0.001) as did SEP (β = 0.086, p = 0.019). Conclusion After CWF cessation in Israel, rates of dental treatments significantly increased. Practical implication By examining accepted notions with up-to-date information, new confirmatory evidence helps decision makers understand the importance of adding fluoride to drinking water.